2022
DOI: 10.1029/2022tc007247
|View full text |Cite
|
Sign up to set email alerts
|

Seismicity Induced at the Northern Dead Sea Transform Fault, Kinneret (Sea of Galilee) Basin, by Shallow Creep Involving a Salt Body

Abstract: The Dead Sea Transform Fault (Figure 1), a sinistral plate boundary (e.g., Freund et al., 1970), is longer than 1000 km and links spreading in the Red Sea with the Anatolian Fault System (Garfunkel, 1981;Sengör, 1979). The N-S-oriented fault has accumulated approximately 100 km of slip since the Neogene (Bartov et al., 1980;Garfunkel, 1981). Freund et al. (1970) and Garfunkel (1981) have suggested that an initial phase of 60 km slip involved pure transform motion, before a divergence component appeared. The so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 79 publications
(204 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, the locations and orientations of the 2018 seismic events are not located along the strike of the suggested secondary fault (Barnea Cohen et al, 2022;Wetzler et al, 2019). The third explanation was recently discussed by Barnea Cohen et al (2022). This study followed the studies of Hamiel et al (2016) and Hamiel and Piatibratova (2021), which found that the northern Jordan Valley segment of the DSF is creeping at shallow depths, and suggested that the shallow creep induces shallow seismic activity beneath the northern part of the Sea of Galilee.…”
Section: 1029/2022gl100584mentioning
confidence: 57%
See 4 more Smart Citations
“…Furthermore, the locations and orientations of the 2018 seismic events are not located along the strike of the suggested secondary fault (Barnea Cohen et al, 2022;Wetzler et al, 2019). The third explanation was recently discussed by Barnea Cohen et al (2022). This study followed the studies of Hamiel et al (2016) and Hamiel and Piatibratova (2021), which found that the northern Jordan Valley segment of the DSF is creeping at shallow depths, and suggested that the shallow creep induces shallow seismic activity beneath the northern part of the Sea of Galilee.…”
Section: 1029/2022gl100584mentioning
confidence: 57%
“…3 of 9 Wetzler et al, 2019). The focal plane solutions of the 2013 and 2018 seismic events indicate normal faulting in the ESE-WNW direction (Barnea Cohen et al, 2022;Wetzler et al, 2019).…”
Section: 1029/2022gl100584mentioning
confidence: 89%
See 3 more Smart Citations